2019
DOI: 10.1007/s00705-019-04172-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and virucidal activity of two recombinant isoforms of phospholipase A2 from Crotalus durissus terrificus venom

Abstract: The global emergence and re-emergence of arthropod-borne viruses (arboviruses) over the past four decades have become a public health crisis of international concern, especially in tropical and subtropical countries. A limited number of vaccines against arboviruses are available for use in humans; therefore, there is an urgent need to develop antiviral compounds. Snake venoms are rich sources of bioactive compounds with potential for antiviral prospection. The major component of Crotalus durissus terrificus ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The virucidal effect was the strongest activity observed for RcP which might suggest that an anti-CHIKV mechanism of action for this complex might be related to a direct action on the viral particle envelope. Previous studies have shown that the virucidal effect of several compounds is closely related to an action on the virus envelope (Tang et al, 1990;Schuhmacher et al, 2003;Carravilla et al, 2017;Kong et al, 2019;Russo et al, 2019). This suggests the existence of interactions between CHIKV envelope glycoproteins and RcP.…”
Section: Discussionmentioning
confidence: 93%
“…The virucidal effect was the strongest activity observed for RcP which might suggest that an anti-CHIKV mechanism of action for this complex might be related to a direct action on the viral particle envelope. Previous studies have shown that the virucidal effect of several compounds is closely related to an action on the virus envelope (Tang et al, 1990;Schuhmacher et al, 2003;Carravilla et al, 2017;Kong et al, 2019;Russo et al, 2019). This suggests the existence of interactions between CHIKV envelope glycoproteins and RcP.…”
Section: Discussionmentioning
confidence: 93%
“…Crotoxin and its CB subunit had antiviral activity not only against Flaviviridae viruses (such as dengue, yellow fever and Zika) but also against Peribunyaviridae and Togaviridae viruses whose envelopes are different, originating from Golgi and plasma membranes, respectively. For example, two recombinant enzymatically active CB variants, CB1 and CB2, showed antiviral effects, not only against dengue, yellow fever and Zika viruses, but also against chikungunya virus ( Togaviridae ) [ 99 ]. In a separate study [ 100 ], crotoxin and its CB subunit were effective against in vitro infection with hepatitis C virus ( Flaviviridae ).…”
Section: Antiviral Activity Of Exogenous Spla 2 Smentioning
confidence: 99%
“…Several natural products have been reported to exert virucidal activity against arthritogenic alphaviruses [ 44 , 45 , 46 ]. Such compounds directly interact with the viral particle, leading to virus inactivation.…”
Section: Antiviral Strategiesmentioning
confidence: 99%
“…Such compounds directly interact with the viral particle, leading to virus inactivation. The phospholipases A2 (PLA2s) from snake ( Crotalus durissus terrificus ) venom have been reported to have a virucidal effect against several enveloped viruses, including CHIKV [ 44 ]. Another example is ginkgolic acid, isolated from the Ginkgo biloba plant, which has been recently shown to inhibit the in vitro replication of CHIKV and MAYV through a direct virucidal effect [ 45 ].…”
Section: Antiviral Strategiesmentioning
confidence: 99%